2016
DOI: 10.1002/16-0108.1
|View full text |Cite
|
Sign up to set email alerts
|

Integrating plant‐ and animal‐based perspectives for more effective restoration of biodiversity

Abstract: Ecological restoration of modified and degraded landscapes is an important challenge for the 21st century, with potential for major gains in the recovery of biodiversity. However, there is a general lack of agreement between plant‐ and animal‐based approaches to restoration, both in theory and practice. Here, we review these approaches, identify limitations from failing to effectively integrate their different perspectives, and suggest ways to improve outcomes for biodiversity recovery in agricultural landscap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
141
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(144 citation statements)
references
References 49 publications
0
141
0
3
Order By: Relevance
“…Numerous studies on reforestation have shown the importance of including tree species that are attractive to animals in order to promote key ecological process, such as pollination and seed dispersal [66,85], that ensure the long-term stability of an ecosystem [86]. Our study showed that though most of the pollination and seed dispersal categories were abundant in habitats under restoration, some habitats lacked certain pollination and seed dispersal categories entirely.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations
“…Numerous studies on reforestation have shown the importance of including tree species that are attractive to animals in order to promote key ecological process, such as pollination and seed dispersal [66,85], that ensure the long-term stability of an ecosystem [86]. Our study showed that though most of the pollination and seed dispersal categories were abundant in habitats under restoration, some habitats lacked certain pollination and seed dispersal categories entirely.…”
Section: Discussionmentioning
confidence: 63%
“…In our study, flowering, pollination and fruiting (Figure 4) observed in both upland and lowland areas of the three-and five-year-old habitats suggest that areas under restoration are Seed dispersal is the last phase in the plant reproductive cycle and the first phase in the process of population renewal [89]. As a result, seedling recruitment is considered to be one of the key factors that determine the success of the long-term vegetation restoration [86]. Restoration habitats that are adjacent to the existing remnant forest are more likely to recover quickly as a result of colonization by animal seed dispersers [18,20,29].…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…freshwater fish, plants, invertebrates) to avoid the current taxonomic bias in the species for which PVAs are implemented in NZ. We believe this may be accomplished by increasing collaboration between researchers, particularly those working with different taxa (McAlpine et al 2016). (2) A continuation of studies on species with lower threat classes should be encouraged especially in taxa where these low threat class species are underrepresented (e.g.…”
Section: Recommendationsmentioning
confidence: 99%